Bagaimana Tingkat Pemahaman Financial Technology dan Financial Literacy Berperan Mengubah Perilaku Konsumsi Pada Generasi Millenial? - Nurcholis Darmawan; Novita Erliana Sari; Maretha Berlianantiya (FISCAL: Jurnal Akuntansi dan Perpajakan, 2023)
AbstractÂ The development of technology and the development of understanding in the community participate in shaping the behavior of the younger generation of Gen Z. This research was carried out at SMA Negeri 1 Madiun which aims to determine the pattern of student consumption behavior amid the rise of technology and various new understandings in society. This study used quantitative research with a sample of 179 students. SPSS v26 was used as a data processing tool in this study. The results showed that financial technology payments on consumption behavior variables showed no reaction. In the financial literacy variable test on consumption behavior variables showed a reaction that led to a significant positive. Then, on the variable of peer conformity to the variable of consumption behavior with positive results. The variables fintech payment financial literacy and peer conformity on consumption behavior have a significant positive effect. This explains that the variables of fintech payment, financial literacy, and peer conformity can simultaneously influence the consumption behavior patterns of SMA Negeri 1 Madiun students.keywords: financial technology, financial literacy, peer conformity, consumption behavior.